Energetic refurbishment of the historic windows of the listed heritage building Alte Schäfflerei and its influence on the overall energy balance. Issue 1 (October 2021) - Bichlmair, S; Krus, M; Merktle, D; Kilian, R
Abstract: This study examines compatibility of monument conservation and modernization of historic windows of old buildings on the example of the Alte Schäfflerei (Old Cooperage) housing the Fraunhofer Centre for Conservation and Energy Performance of Historic Buildings at Benediktbeuern monastery. Several historic windows are extended to box-type windows and examined in detail. The calculation of the thermal bridges and the resulting U-values of the windows as well as the linear thermal bridge heat loss coefficients result in a reliable estimation of the thermal behaviour of the box-type windows. Via measurements of the surface temperature and heat fluxes on a box-type window the thermal resistance and heat transfer coefficient are estimated. The heat transfer coefficient is calculated in accordance to DIN 10077 with simple and detailed calculation and compared to the estimated calculation of simplified measurements. The energy efficiency of the whole building of the Old Cooperage is calculated in accordance to DIN V 18599 and shows the rate of heat losses of the windows compared to the overall energy demand of the building. For this purpose, the Old Cooperage is implemented with a hypothetical historic usage in DIN V 18599.